ANALYSIS OF COMPANIES’ CHARACTERISTICS, ECONOMIC CONDITIONS, NET PREMIUMS, AND THEIR IMPACTS ON PROFITABILITY - Ruchiyat, Endang Heddy (JBFEM, 2020)
This research is aimed at empirically testing insurance companies’ profitability and net premiums from the variables of company size, solvability, gross domestic products, and inflation. The research was conducted on general insurance companies in Indonesia observed throughout 2013 – 2017 using the panel data regression. The research results showed: First, company size, solvability, gross domestic products, and inflation have a significant influence on net premiums through the common model effect; secondly, net premiums have a significant influence on profitability through the fixed effect model. This research is expected to be a recommendation and information to the insurance industry, associations, and policymakers.